Hybrid zinc-air battery positive electrode material, battery and preparation method thereof

The positive electrode material for hybrid zinc-air batteries was prepared by growing nanowires, nanosheets and nanoribbon array crosslinking structures of cobalt oxides, cobalt sulfides, silver and silver sulfides on a foam nickel substrate, and the solution was solved The output voltage fluctuations, rate performance and Coulomb efficiency are not ideal, and the cycle stability are poor, which achieve efficient and stable battery performance.

CN119495756APending Publication Date: 2025-02-21GUANGDONG UNIV OF PETROCHEMICAL TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411661735.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing hybrid zinc-air batteries have problems such as fluctuations in output voltage, poor rate performance and Coulomb efficiency, and poor long-term charge and discharge cycle stability under high area capacity conditions.

Method used

The nanowires, nanosheets and nanoribbon array crosslinked structures composed of cobalt oxides, cobalt sulfides, silver and silver sulfides grown on the foam nickel substrate are used as the positive electrode material of hybrid zinc-air batteries, and are subject to hydrothermal reaction. The material was prepared by vulcanization treatment.

Benefits of technology

It realizes the output of a straight high-voltage discharge platform, improves the battery charge and discharge reversibility and Coulomb efficiency, and enhances the long-term charge and discharge cycle stability under high area capacity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495756A_ABST
    Figure CN119495756A_ABST
Patent Text Reader

Abstract

The invention discloses a hybrid zinc-air battery positive electrode material, a battery and a preparation method of the hybrid zinc-air battery positive electrode material. According to the positive electrode material, a cross-linked structure of a nanowire array, a nanosheet array and a nanobelt array which are composed of cobalt oxide, cobalt sulfide, silver and silver sulfide grows on a foamed nickel substrate; the hybrid zinc-air battery can output a straight discharge platform with relatively high voltage, so that the problem of output voltage fluctuation of an existing hybrid zinc-air battery positive electrode material is solved; a nanowire and nanosheet or nanobelt array cross-linked structure directly grows on the foamed nickel substrate, so that more active reaction sites can be exposed, the electrochemical reaction accessibility of the material and the synergistic effect of various active reaction sites are enhanced, the charge-discharge reversibility of the positive electrode material is improved, and the service life of the positive electrode material is prolonged. The problems that the rate capability and coulombic efficiency are not ideal, and the long-term charge-discharge cycle stability is poor under the condition of high area capacity are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zinc-air batteries, and in particular to a hybrid zinc-air battery positive electrode material, and preparation and application thereof. Background Art

[0002] Aqueous zinc-air batteries use metallic zinc as the negative electrode. Zinc has a low redox potential, is abundant in resources, low in cost, environmentally friendly, compatible with water, easy to assemble, and has great advantages in safety. The positive electrode active material does not need to be stored in the battery, but is continuously taken from the oxygen in the surrounding air, so it has a high theoretical energy density (1086Wh kg -1 ).

[0003] However, due to the slow oxygen reduction (ORR) / oxygen evolution reaction (OER) process at the cathode, the overpotential is large (about 0.7V), the actual discharge voltage is generally lower than 1.4V, and the actual energy density is still low (<200Wh·kg -1 ). Rechargeable alkaline zinc-metal batteries, especially Zn-Ag batteries, have an operating voltage of up to 1.85V, but are limited by low energy density and short cycle life in practical applications. Zinc-metal batteries and zinc-air batteries use the same electrolyte system and zinc negative electrode. Therefore, the two can be organically combined and integrated into one battery, sharing a zinc negative electrode to form a hybrid zinc-air battery, which has the advantages of high operating voltage of zinc-metal batteries and high energy density of zinc-air batteries. The positive electrode material of the hybrid zinc-air battery should be multifunctional. During charging and discharging, the positive electrode material is both an electrocatalyst for catalyzing ORR / OER in the zinc-air battery and an active substance in the zinc-metal battery, which undergoes a Faraday redox reaction.

[0004] Although hybrid zinc-air batteries have made certain technological progress, they still have the following problems: First, they generally have two or three discharge platforms, one high and one low, and the output voltage will inevitably fluctuate. The low voltage platform will also lead to a decrease in energy density. Second, the coulombic efficiency and rate performance are not ideal. In addition, the long-term charge and discharge cycle stability under high area capacity conditions is still some distance away from practical application, and there is still much room for improvement. Summary of the invention

[0005] In view of this, the present disclosure provides a hybrid zinc-air battery positive electrode material, a battery and a preparation method thereof, which are used to solve the problems of output voltage fluctuation, unsatisfactory rate performance and coulombic efficiency, and poor long-term charge and discharge cycle stability under high area capacity conditions in existing hybrid zinc-air batteries.

[0006] To achieve the above-mentioned object of the invention, in the first aspect, the positive electrode material of the hybrid zinc-air battery, the positive electrode material is:

[0007] Cross-linked structures of nanowire arrays, nanosheet arrays and nanobelt arrays composed of cobalt oxide, cobalt sulfide, silver and silver sulfide are grown on a nickel foam substrate.

[0008] In the present disclosure and possible embodiments, the cobalt oxide is CoO(OH) and Co3O4, the cobalt sulfide is Co8S9, and the silver sulfide is Ag2S.

[0009] In a second aspect, the hybrid zinc-air battery comprises:

[0010] The positive electrode material of the first aspect; the negative electrode of the battery is a zinc-free negative electrode with a copper mesh as the current collector, and the electrolyte is a 0.1-0.2 mol·L -1 4~6mol·L of zinc oxide or zinc acetate -1 Aqueous KOH solution.

[0011] In a third aspect, a method for preparing the hybrid zinc-air battery positive electrode material according to the first aspect comprises:

[0012] Growing a cobalt oxide nanowire array on a nickel foam substrate to prepare a first intermediate material;

[0013] introducing silver onto the first intermediate material to obtain a second intermediate material;

[0014] The second intermediate material is sulfurized to obtain the hybrid zinc-air battery positive electrode material.

[0015] In the present disclosure and possible embodiments, the method of growing a cobalt oxide nanowire array on a nickel foam substrate to prepare a first intermediate material comprises:

[0016] Cobalt salt and urea are weighed in a set ratio and dissolved in deionized water to prepare a solution, and the nickel foam is immersed in the solution for a hydrothermal reaction. A cobalt oxide nanowire array is grown on the nickel foam substrate through the hydrothermal reaction to obtain the first intermediate material.

[0017] In the present disclosure and possible embodiments, the cobalt salt is one of cobalt nitrate, cobalt chloride and cobalt sulfate, and the molar ratio of the cobalt salt to the urea is 1:1 to 1:2;

[0018] The hydrothermal reaction temperature ranges from 120° C. to 150° C., and the hydrothermal reaction time ranges from 12 h to 18 h. After the hydrothermal reaction is completed, the first intermediate material is washed with deionized water for 3 to 5 times.

[0019] In the present disclosure and possible embodiments, the method of introducing silver into the first intermediate material to obtain the second intermediate material includes:

[0020] The first intermediate material is immersed in a silver nitrate solution and reacted at room temperature for 10 minutes to 60 minutes to obtain the second intermediate material.

[0021] In the present disclosure and possible embodiments, the concentration of the silver nitrate solution is 50 mmol·L -1 ~100mmol·L -1 .

[0022] In the present disclosure and possible embodiments, the method of sulfurizing the prepared second intermediate material to prepare the hybrid zinc-air battery positive electrode material includes:

[0023] The second intermediate material is immersed in a sulfur source solution, and the second intermediate material is sulfurized by a hydrothermal reaction. After sulfurization, the positive electrode material is obtained by washing with water and vacuum drying.

[0024] In the present disclosure and possible embodiments, the sulfur source is sodium thiosulfate or thiourea, and the concentration of the sulfur source is 7 mmol·L -1 ~28mmol·L -1 ;

[0025] The hydrothermal vulcanization reaction temperature is 120°C to 150°C, the hydrothermal reaction vulcanization time is 12h to 18h, and the positive electrode material after hydrothermal reaction vulcanization is washed 3 to 5 times with deionized water; the vacuum drying temperature is 60°C to 80°C, and the drying time is 2h to 4h;

[0026] The nickel foam is pretreated by immersing the nickel foam in anhydrous ethanol and ultrasonically treating the nickel foam for 20 minutes to 30 minutes. After the ultrasonic treatment, the nickel foam is rinsed with deionized water and dried at 60°C.

[0027] Beneficial effects of the present invention:

[0028] (1) The hybrid zinc-air battery cathode material disclosed in the present invention has excellent catalytic ORR / OER activity and Faraday reaction activity, and can output a flat discharge platform with a relatively high voltage, thus solving the output voltage fluctuation problem of the existing hybrid zinc-air battery cathode material;

[0029] (2) The cross-linked structure of nanowires, nanosheets and nanobelt arrays grown directly on the nickel foam substrate is conducive to exposing more active reaction sites, enhancing the electrochemical reaction accessibility of the material, and the synergistic effect of various active reaction sites improves the charge and discharge reversibility of the battery, solving the problems of unsatisfactory rate performance and coulombic efficiency as well as poor long-term charge and discharge cycle stability under high area capacity conditions;

[0030] (3) The hybrid zinc-air battery constructed using the positive electrode material prepared by the present invention has a -2Under the condition of 10 ... -2 ; At current densities up to 40 mA cm -2 Coulombic efficiency and discharge area capacity at 10 mA cm -2 Basically the same, the discharge voltage platform is still maintained above 1.51V, with excellent discharge rate performance; BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The above and other objects, features and advantages of the present disclosure will become more apparent through the following description of the embodiments of the present disclosure with reference to the accompanying drawings, in which:

[0032] Figure 1 ai are SEM images of the first intermediate material, the second intermediate material and the positive electrode material prepared in Example 1 at different magnifications;

[0033] Figure 2 af are the EDS characterization element distribution of the positive electrode material prepared in Example 1;

[0034] Figure 3 This is the EDS spectrum of the positive electrode material prepared in Example 1;

[0035] Figure 4 is the XRD spectrum of the positive electrode material prepared in Example 1;

[0036] Figure 5 is the long-term charge and discharge curve of the hybrid zinc-air battery prepared in Example 1;

[0037] Figure 6 is the long-term charge and discharge performance of the hybrid zinc-air battery prepared in Example 1;

[0038] Figure 7 This is a representative single cycle charge and discharge curve of the hybrid zinc-air battery prepared in Example 1 for long-term charge and discharge;

[0039] Figure 8 is the charge and discharge performance of the hybrid zinc-air battery prepared in Example 2;

[0040] Fig. 9 is the charge and discharge performance of the hybrid zinc-air battery prepared in Example 3;

[0041] Fig.10 is the charge and discharge performance of the hybrid zinc-air battery prepared in Example 4;

[0042] Fig.11is the charge and discharge performance of the hybrid zinc-air battery prepared in Example 5;

[0043] Fig.12 It is a comparison of the charge and discharge voltage platform curves of typical single cycles of Examples 1 to 5;

[0044] Fig.13 is the discharge rate performance of the hybrid zinc-air battery prepared in Example 1;

[0045] Fig.14 1 is a typical discharge curve of the hybrid zinc-air battery prepared in Example 1 at different discharge currents;

[0046] Fig.15 It is the charge and discharge performance of the hybrid zinc-air battery prepared in the comparative example. DETAILED DESCRIPTION

[0047] The present disclosure is described below based on embodiments, but it is worth noting that the present disclosure is not limited to these embodiments. In the detailed description of the present disclosure below, some specific details are described in detail. However, for the parts that are not described in detail, those skilled in the art can also fully understand the present disclosure.

[0048] The method for preparing a positive electrode material for a hybrid zinc-air battery provided in an embodiment of the present disclosure specifically comprises the following steps:

[0049] 1. Growth of cobalt oxide nanowire arrays on nickel foam substrate:

[0050] The growth method comprises weighing cobalt salt and urea in a certain proportion and dissolving them in deionized water to prepare a solution, immersing the nickel foam in the solution, and then performing a hydrothermal reaction to grow a cobalt oxide nanowire array on the nickel foam substrate to obtain a first intermediate material.

[0051] In a specific embodiment, the nickel foam is pretreated, and the pretreatment process is: immersing the nickel foam in anhydrous ethanol, ultrasonically treating it for 20 minutes to 30 minutes to remove surface organic matter and floating dust, and then rinsing it with deionized water after ultrasonic treatment, and drying it at 60°C.

[0052] In a specific embodiment, the cobalt salt is one of cobalt nitrate, cobalt chloride and cobalt sulfate, and the molar ratio of the cobalt salt to urea is 1:1 to 1:2; the hydrothermal reaction is carried out in a hydrothermal reactor with a polytetrafluoroethylene lining, the hydrothermal reaction temperature ranges from 120°C to 150°C, the hydrothermal reaction time is 12h to 18h, and after the hydrothermal reaction is completed, the obtained first intermediate material is washed 3 to 5 times with deionized water.

[0053] 2. Introducing silver into the prepared first intermediate material:

[0054] The introduction method is to immerse the first intermediate material in a silver nitrate solution and react at room temperature for 10 minutes to 60 minutes, thereby introducing silver on the surface of the first intermediate material to obtain the second intermediate material.

[0055] In a specific embodiment, the concentration of the silver nitrate solution is 50 mmol·L -1 ~100mmol·L -1 .

[0056] 3. Vulcanize the obtained second intermediate material:

[0057] The sulfurization method comprises immersing the second intermediate material in a sulfur source solution, sulfurizing the second intermediate material through a hydrothermal reaction, and obtaining the desired positive electrode material after water washing and vacuum drying after sulfurization.

[0058] In a specific embodiment, the sulfur source is one of sodium thiosulfate (Na2S2O3) and thiourea, and the concentration of the sulfur source is 7 mmol·L -1 ~28mmol·L -1 .

[0059] In a specific embodiment, the hydrothermal reaction vulcanization is carried out in a hydrothermal reactor with a polytetrafluoroethylene lining; the hydrothermal reaction vulcanization temperature range is 120°C to 150°C, the hydrothermal reaction vulcanization time is 12h to 18h, and the positive electrode material after hydrothermal reaction vulcanization is washed with deionized water 3 to 5 times; the vacuum drying temperature range is 60°C to 80°C, and the drying time is 2h to 4h.

[0060] The hybrid zinc-air battery assembled by the positive electrode material prepared by the above method provided in the embodiment of the present disclosure comprises a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode is a zinc-free negative electrode with a copper mesh as a current collector; the electrolyte is a 0.1-0.2 mol·L -1 4-6 mol·L of zinc oxide (ZnO) or zinc acetate (Zn(CH2COO)2) -1 Aqueous KOH solution.

[0061] The following are preferred embodiments of the present disclosure and corresponding comparative examples. The beneficial effects of the positive electrode material and battery of the present invention are illustrated through the performance test data of the embodiments and comparative examples.

[0062] Example 1

[0063] 1. The positive electrode material used in the hybrid zinc-air battery of this embodiment 1 is a nanowire and nanosheet or nanobelt array composed of cobalt oxide, cobalt sulfide, silver and silver sulfide grown on a nickel foam substrate. The specific preparation method is as follows:

[0064] (1) Pretreatment of nickel foam: immerse the nickel foam in anhydrous ethanol and perform ultrasonic treatment for 20 min to 30 min to remove organic matter and floating dust on the surface, then rinse with deionized water and dry at 60 °C.

[0065] (2) Weigh 5 mmol of cobalt nitrate (Co(NO3)2·6H2O) and 10 mmol of urea respectively and add them to 60 mL of deionized water. After fully stirring, transfer the solution into a 100 mL stainless steel hydrothermal reactor with a polytetrafluoroethylene liner, and then immerse the pretreated nickel foam into the solution; perform a hydrothermal reaction at 120°C for 12 hours, cool naturally to room temperature after the reaction, take out the nickel foam, and then wash it with deionized water for 3 times to obtain a first intermediate material.

[0066] (3) The first intermediate material obtained in step (2) is immersed in 10 mL of 100 mmol / L -1 The reaction was carried out in a silver nitrate solution at room temperature for 10 minutes, and the nickel foam was taken out and washed with deionized water for 3 times to obtain a second intermediate material.

[0067] (4) Weigh 0.7 mmol of sodium thiosulfate (Na2S2O3) and add it to 50 mL of deionized water. Stir thoroughly to obtain a concentration of 14 mmol / L -1 Sodium thiosulfate solution is transferred into a 100 mL stainless steel hydrothermal reactor with a polytetrafluoroethylene liner, and the second intermediate material obtained in step (3) is placed in it. The reaction is carried out at 120°C for 12 hours. After the reaction is completed, it is naturally cooled to room temperature. The nickel foam is taken out, washed with deionized water for 3 times, and vacuum dried at 60°C for 2 hours to obtain the positive electrode material of Example 1.

[0068] 2. Preparation of Hybrid Zinc-Air Battery of Example 1:

[0069] Pure copper mesh was used as the negative electrode current collector, and the positive electrode material of Example 1 was used as the positive electrode, with a content of 0.2 mol·L -1 6 mol·L ZnO -1 Hybrid zinc-air batteries were assembled using KOH solution as electrolyte.

[0070] Example 2

[0071] The difference from Example 1 is that in step (3), the concentration of the silver nitrate solution is changed, specifically: the first intermediate material prepared in step (2) is immersed in 10 mL of a 50 mmol·L -1 The reaction was carried out in a silver nitrate solution at room temperature for 10 min, the nickel foam was taken out, and washed with deionized water for 3 times. The other steps were the same as those in Example 1.

[0072] Example 3

[0073] The difference from Example 1 is that in step (3), the reaction time is changed, specifically: the first intermediate material prepared in step (2) is immersed in 10 mL of a 100 mmol·L -1 The reaction was carried out in a silver nitrate solution at room temperature for 60 min, the nickel foam was taken out, and washed with deionized water for 3 times. The other steps were the same as those in Example 1.

[0074] Example 4

[0075] The difference from Example 1 is that in step (4), the concentration of the sodium thiosulfate solution is changed, specifically: 0.35 mmol of sodium thiosulfate (Na2S2O3) is weighed and added to 50 mL of deionized water, and stirred thoroughly to obtain a concentration of 7 mmol·L -1 Sodium thiosulfate solution, transfer the solution into 100 mL of

[0076] In a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, the hydrothermal reaction was carried out at 120° C. for 12 h. After the reaction was completed, it was naturally cooled to room temperature. The nickel foam was taken out and washed three times with deionized water. The other steps were the same as in Example 1.

[0077] Example 5

[0078] The difference from Example 1 is that in step (4), the concentration of the sodium thiosulfate solution is changed, specifically: 1.40 mmol of sodium thiosulfate (Na2S2O3) is weighed and added to 50 mL of deionized water, and stirred thoroughly to obtain a concentration of 28 mmol·L -1 Sodium thiosulfate solution was transferred into a 100 mL stainless steel hydrothermal reactor with a polytetrafluoroethylene liner, and hydrothermally reacted at 120° C. for 12 h. After the reaction was completed, it was naturally cooled to room temperature, and the nickel foam was taken out and washed with deionized water for 3 times. The other steps were the same as in Example 1.

[0079] Characterization of positive electrode materials of Examples 1 to 5 and performance testing of hybrid zinc-air batteries

[0080] (1) SEM characterization of cathode materials:

[0081] Figure 1 The intermediate material and the positive electrode material of Example 1 were characterized by scanning electron microscopy (SEM), wherein Figure 1 a The low magnification SEM image of the first intermediate material shows that a dense coating grows on the nickel foam skeleton after hydrothermal treatment, which has two morphologies: relatively flat and hemispherical protrusions; Figure 1 b is a high magnification SEM image of the flat area, from which it can be seen that the relatively flat area on the coating mainly presents a nanowire array structure; Figure 1c is an enlarged SEM image of the hemispherical raised area. It can be seen that the raised area on the coating is mainly a nanowire array that grows in a hemispherical radial form. Figure 1 d is a low magnification SEM image of the second intermediate material. It can be seen that the dense coating on the nickel foam skeleton is still tightly attached to the nickel foam after the reaction with silver nitrate, and its morphology has changed slightly; the relatively flat area ( Figure 1 e) and raised area ( Figure 1 f) The nanowires evolved into an interwoven morphology, indicating that the second intermediate material after hydrothermal treatment underwent a replacement reaction with silver nitrate (Co 2+ +Ag + =Co 3+ +Ag) causes its morphology to change; Figure 1 g is a low magnification SEM image of the final prepared cathode material. It can be seen that the morphology of the coating tightly attached to the nickel foam after the second intermediate material and Na2S2O3 hydrothermal sulfidation has further changed, and the relatively flat area ( Figure 1 h) and raised area ( Figure 1 i) further evolved into a complex cross-linked structure mainly composed of nanowires, nanosheets and nanobelts, indicating that a certain sulfurization reaction occurred between the second intermediate material and Na2S2O3 during hydrothermal sulfurization.

[0082] (2) Characterization of elemental composition of positive electrode materials:

[0083] The element composition of the positive electrode material of Example 1 was characterized by X-ray photoelectron spectroscopy (EDS). Figure 2 and Figure 3 ,Depend on Figure 2 It can be seen that the surface of the positive electrode material grown on the nickel foam is mainly uniformly distributed with Ni, Co, Ag, O and S elements. Figure 3 The results show that the atomic percentage contents of these elements are 32.87%, 13.15%, 0.16%, 53.43% and 0.39%, respectively, which further illustrates that the surface of the synthesized positive electrode material is mainly composed of Ni, Co and O elements, with less Ag species and S species.

[0084] (3) XRD analysis of positive electrode materials:

[0085] The positive electrode material obtained in Example 1 was subjected to X-ray diffraction (XRD) analysis. Figure 2It can be seen that in addition to the diffraction peaks at 2θ = 44.5°, 51.8° and 76.4° of the nickel foam substrate, the diffraction peaks at 2θ = 17.7°, 19.5°, 34.3° and 44.6° are attributed to the CoO(OH) crystal phase (PDF 02-0214), the diffraction peaks at 2θ = 19.0°, 31.3°, 38.5°, 59.4° and 65.2° are attributed to the Co3O4 crystal phase (PDF 42-1467); the diffraction peaks at 2θ = 17.8°, 29.9°, 36.1°, 39.5°, 47.4 and 51.9° are attributed to the Co8S9 crystal phase (PDF19-0364), indicating that the Co on the material exists in the form of CoO(OH), Co3O4 and Co8S9. The diffraction peaks at 2θ = 37.9° and 44.1° are attributed to Ag. 0 The diffraction peaks at 2θ = 24.9°, 33.6°, 44.2°, 46.2°, 50.7°, 54.2°, 59.4° and 62.6° are in good agreement with the crystal phase of Ag2S (PDF 14-0072), indicating that the Ag on the material is Ag 0 And Ag2S crystal phase exists.

[0086] (4) Charge and discharge performance test of hybrid zinc-air battery:

[0087] Pure copper mesh was used as the negative electrode current collector, and the positive electrode materials prepared in Examples 2 to 5 were used as the positive electrode, respectively, with a content of 0.2 mol·L -1 6 mol·L ZnO -1 The hybrid zinc-air battery was assembled with KOH solution as electrolyte. The charge and discharge performance of the assembled hybrid zinc-air battery was tested using the CT-4008 battery test system of Shenzhen Xinwei Electronics Co., Ltd. at a current density of 10 mA cm -2 Charge for 24 minutes (charging area capacity is 4 mAh cm -2 ), open circuit and let stand for 2 min, then at 10 mA cm -2 The battery is discharged at a current density of 0.9 V to a cut-off voltage of 0.9 V.

[0088] Figure 5 to Figure 7 The test results of the charge and discharge performance of the hybrid zinc-air battery assembled with the positive electrode material prepared in Example 1 show that the charge area capacity is as high as 4 mAh·cm -2 The charge and discharge coulomb efficiency gradually increased from 93.1% in the first cycle and stabilized at more than 95% after the 100th cycle (discharge area capacity at 3.8 mAh cm -2 Above), up to 100% (discharge area capacity up to 4 mAh cm -2 )( Figure 5 and Figure 6 ), and achieved efficient and stable charge and discharge cycles of 1600 times (about 1333h) under high area capacity conditions. At the same time, the charging voltage was between 1.84 and 1.90V, and the discharge voltage of most charge and discharge cycles was above 1.67V. After 1500 cycles, the discharge voltage decreased, and the discharge voltage of the last cycle was still as high as 1.64V ( Figure 6 ), all charge and discharge cycles have a relatively high flat voltage platform ( Figure 7 ). Compared with the silver-based cathode material described in the background art, the positive electrode material prepared in Example 1 solves the problems of discharge voltage fluctuation, low coulombic efficiency, and poor long-term charge and discharge cycle stability under high area capacity conditions.

[0089] According to the same method as in Example 1, the hybrid zinc-air batteries prepared in Examples 2 to 5 were tested for 50 cycles of charge and discharge performance. Figure 8 to Figure 11 .from Figure 8 to Figure 11 It can be seen that at high charge area capacity (4 mAh cm -2 ), the charging voltage of the hybrid zinc-air batteries prepared in Examples 2 to 5 was about 1.85 V, the discharging voltage was above 1.65 V, the coulomb efficiency was about 95%, and the discharge area capacity could reach 3.8 mAh·cm -2 about. Fig.12 The typical single cycle charge and discharge voltage platform curves of Examples 1 to 5 are compared. Fig.12 It can be seen that, basically equivalent to Example 1, the hybrid zinc-air batteries prepared in Examples 2 to 5 also obtained a flat discharge platform with a relatively high voltage.

[0090] (5) Discharge rate performance test of hybrid zinc-air battery:

[0091] At a current density of 10 mA cm -2 Charge for 24 minutes (charging area capacity is 4 mAh cm -2 ), open circuit and let stand for 2 min, then gradually increase the discharge current density to 10 mA cm -2 、15mA·cm -2 , 20mA·cm -2 , 25mA·cm -2 、30mA·cm -2 、35mA·cm -2 , 40mA·cm -2 Finally, it returns to 10 mA cm -2 The current density was discharged to a cut-off voltage of 0.9V, and the discharge rate performance was tested. The results are shown in Fig.13 and Fig.14 ,Depend on Fig.13 and Fig.14 It can be seen that as the discharge current increases, the discharge voltage and discharge platform gradually decrease, and the current density increases to 40 mA cm -2 When the current density is restored to 10 mA cm -2 When the discharge current is increased, the discharge voltage and discharge platform can be completely restored to the level before the discharge current is increased, while the battery discharge area capacity (Coulomb efficiency) remains basically unchanged when the discharge current increases, and can be stabilized at 3.8 mAh cm -2 The above (Coulomb efficiency is above 95%), which shows that the hybrid zinc-air battery assembled with the cathode material of Example 1 has excellent discharge rate performance, which is better than the silver-based cathode material described in the background technology.

[0092] Comparative Example

[0093] In order to examine the effect of the introduction of silver, a positive electrode material without the introduction of silver was prepared. The preparation method was different from that of Example 1 in that step (3) was omitted and the other steps were the same as those of Example 1.

[0094] The charge and discharge performance of the prepared positive electrode material is as follows Fig.15 As shown, it can be seen that the discharge voltage of the positive electrode material without the introduction of silver is around 1.66V, but the charge and discharge coulomb efficiency and discharge area capacity fluctuate violently with the increase in the number of discharge cycles and cannot operate stably.

[0095] The above-described embodiments are only embodiments of the present disclosure, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the present disclosure. It should be noted that, for a person of ordinary skill in the art, without departing from the concept of the present disclosure, several variations, equivalent substitutions, improvements, etc. may be made, all of which fall within the scope of protection of the present disclosure. Therefore, the scope of protection of the present disclosure shall be subject to the attached claims.

Claims

1. A hybrid zinc-air battery positive electrode material, characterized in that: The positive electrode material is: Cross-linked structures of nanowire arrays, nanosheet arrays and nanobelt arrays composed of cobalt oxide, cobalt sulfide, silver and silver sulfide are grown on a nickel foam substrate.

2. The hybrid zinc-air battery positive electrode material according to claim 1, characterized in that: The cobalt oxides are CoO(OH) and Co3O4, the cobalt sulfide is Co8S9, and the silver sulfide is Ag2S.

3. A hybrid zinc-air battery, characterized in that: include: The positive electrode material according to claim 1 or 2; the negative electrode of the battery is a zinc-free negative electrode with a copper mesh as a current collector, and the electrolyte is a 0.1-0.2 mol·L -1 4~6mol·L of zinc oxide or zinc acetate -1 Aqueous KOH solution.

4. The method for preparing the hybrid zinc-air battery positive electrode material according to claim 1 or 2, characterized in that: include: Growing a cobalt oxide nanowire array on a nickel foam substrate to prepare a first intermediate material; introducing silver onto the first intermediate material to obtain a second intermediate material; The second intermediate material is sulfurized to obtain the hybrid zinc-air battery positive electrode material.

5. The method for preparing a hybrid zinc-air battery according to claim 4, characterized in that: The method of growing a cobalt oxide nanowire array on a nickel foam substrate to prepare a first intermediate material comprises: Cobalt salt and urea are weighed in a set ratio and dissolved in deionized water to prepare a solution, and the nickel foam is immersed in the solution for a hydrothermal reaction. A cobalt oxide nanowire array is grown on the nickel foam substrate through the hydrothermal reaction to obtain the first intermediate material.

6. The method for preparing a hybrid zinc-air battery according to claim 5, characterized in that: The cobalt salt is one of cobalt nitrate, cobalt chloride and cobalt sulfate, and the molar ratio of the cobalt salt to the urea is 1:1 to 1:2; The hydrothermal reaction temperature ranges from 120° C. to 150° C., and the hydrothermal reaction time ranges from 12 h to 18 h. After the hydrothermal reaction is completed, the first intermediate material is washed with deionized water for 3 to 5 times.

7. The method for preparing a hybrid zinc-air battery according to claim 6, characterized in that: The method of introducing silver into the first intermediate material to obtain the second intermediate material comprises: The first intermediate material is immersed in a silver nitrate solution and reacted at room temperature for 10 minutes to 60 minutes to obtain the second intermediate material.

8. The method for preparing a hybrid zinc-air battery according to claim 7, characterized in that: The concentration of the silver nitrate solution is 50 mmol·L -1 ~100mmol·L -1 .

9. The method for preparing a hybrid zinc-air battery according to claim 8, characterized in that: The method of sulfurizing the prepared second intermediate material to prepare the hybrid zinc-air battery positive electrode material comprises: The second intermediate material is immersed in a sulfur source solution, and the second intermediate material is sulfurized by a hydrothermal reaction. After sulfurization, the positive electrode material is obtained by washing with water and vacuum drying.

10. The method for preparing a hybrid zinc-air battery according to claim 9, characterized in that: The sulfur source is sodium thiosulfate or thiourea, and the concentration of the sulfur source is 7 mmol·L -1 ~28mmol·L -1 ; The hydrothermal vulcanization reaction temperature is 120°C to 150°C, the hydrothermal reaction vulcanization time is 12h to 18h, and the positive electrode material after hydrothermal reaction vulcanization is washed 3 to 5 times with deionized water; the vacuum drying temperature is 60°C to 80°C, and the drying time is 2h to 4h; The nickel foam is pretreated by immersing the nickel foam in anhydrous ethanol and ultrasonically treating the nickel foam for 20 minutes to 30 minutes. After the ultrasonic treatment, the nickel foam is rinsed with deionized water and dried at 60°C.